2020
DOI: 10.1089/neu.2020.7030
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Walking in Incomplete Spinal Cord Injury: Role of Corticospinal Control

Abstract: Locomotor recovery after incomplete spinal cord injury (iSCI) is influenced by spinal and supraspinal networks. Conventional clinical gait analysis fails to differentiate between these components. There is evidence that corticospinal control is enhanced during targeted walking, where each foot must be continuously placed on visual targets in randomized order. This study investigates the potential of targeted walking in the functional assessment of corticospinal integrity. Twenty-one controls and 16 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…α-errors of p < 0.05 were considered significant. Prior to the data analysis, the two legs of each participant were grouped into more and less affected sides, based on the total lower extremity motor scores (LEMS) per leg [66][67][68]. In participant 7, total light touch sensory scores were additionally considered, as LEMS were equivalent in both legs.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…α-errors of p < 0.05 were considered significant. Prior to the data analysis, the two legs of each participant were grouped into more and less affected sides, based on the total lower extremity motor scores (LEMS) per leg [66][67][68]. In participant 7, total light touch sensory scores were additionally considered, as LEMS were equivalent in both legs.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…Similarly, wavelet analysis can characterize the time–frequency profile of the sEMG signal with good resolution and contribute to the understanding of targeted walking and corticospinal integrity. Using such techniques, it was shown that an increase of relative semitendinosus intensity in the 38-Hz band during the swing phase was related to targeted walking in SCI, likely reflecting greater corticospinal control before heel-strike during targeted walking [ 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…PS mainly demonstrates whether the animal achieves the swing phase, whereas GS additionally estimates the stability and consistency of the stepping process. In primates, highly stable and consistent gait cycles (GS) require more precise supraspinal control than achieving swing (PS) [ 27 , 60 , 61 ]. The integrity of cortical projection pathways determines the degree of supraspinal control after SCI.…”
Section: Discussionmentioning
confidence: 99%